Interventional vitamin C: A strategy for attenuation of coagulopathy and inflammation in a swine multiple injuries model. Issue 1 (July 2018) - Reynolds, Penny S.; Fisher, Bernard J.; McCarter, Jacquelyn; Sweeney, Christopher; Martin, Erika J.; Middleton, Paul; Ellenberg, Matthew; Fowler, Evan; Brophy, Donald F.; Fowler, Alpha A.; Spiess, Bruce D.; Natarajan, Ramesh
Abstract : BACKGROUND: Coagulopathy and inflammation induced by hemorrhagic shock and traumatic injury are associated with increased mortality and morbidity. Vitamin C (VitC) is an antioxidant with potential protective effects on the proinflammatory and procoagulant pathways. We hypothesized that high-dose VitC administered as a supplement to fluid resuscitation would attenuate inflammation, coagulation dysfunction, and end-organ tissue damage in a swine model of multiple injuries and hemorrhage. METHODS: Male Sinclair swine (n = 24; mean body weight, 27 kg) were anesthetized, intubated, mechanically ventilated, and instrumented for physiologic monitoring. Following stabilization, swine were subjected to shock/traumatic injury (hypothermia, liver ischemia and reperfusion, comminuted femur fracture, hemorrhagic hypotension), resuscitated with 500 mL of hydroxyethyl starch, and randomized to receive either intravenous normal saline (NS), low-dose VitC (50 mg/kg; LO), or high-dose VitC (200 mg/kg; HI). Hemodynamics, blood chemistry, hematology, and coagulation function (ROTEM) were monitored to 4 hours postresuscitation. Histological and molecular analyses were obtained for liver, kidney, and lung. RESULTS: Compared with VitC animals, NS swine showed significant histological end-organ damage, elevated acute lung injury scores, and increased mRNA expression of tissue proinflammatory mediators (IL-1β, IL-8, TNFα), plasminogen activation inhibitor-1 and tissue factor. There were no statistically significant differences between treatment groups on mean arterial pressure or univariate measures of coagulation function; however, NS showed impaired multivariate clotting function at 4 hours. CONCLUSION: Although correction of coagulation dysfunction was modest, intravenous high-dose VitC may mitigate the proinflammatory/procoagulant response that contributes to multiple organ failure following acute severe multiple injuries. LEVEL OF EVIDENCE: Prospective randomized controlled blinded trial study, Preclinical (animal-based). Abstract : Supplemental digital content is available in the text.